DA'WAH AND DIGITALIZATION: NURUL AZKA COMEDY'S DA'WAH STRATEGY THROUGH THE INSTAGRAM PLATFORM - Ida Selviana Masruroh (KOMUNIKE: Jurnal Komunikasi Penyiaran Islam, 2022)
Da'wah media continues to undergo remarkable development. The emergence of social media participates in the influence of Da'i's da'wah message delivery efforts on Mad'u, especially Instagram. This research was conducted on Nurul Azka's personal Instagram account, @nunuzoo, utilizing the Virtual Ethnography Method with Milles and Huberman Analysis. The results suggest that @nunuzoo from the da'wah approach utilized on Instagram has a strategy, namely generating funny da'wah video themes with viral events and short video durations that do not bore the audience. Supporting aspects are based on hobbies and have creativity, while hindering factors are not having a team and trouble managing time when filming comedy da'wah films.